2007
DOI: 10.3201/eid1305.061489
|View full text |Cite
|
Sign up to set email alerts
|

International Spread of Multidrug-resistantSalmonellaSchwarzengrund in Food Products

Abstract: This serovar was isolated from persons, food, and food animals in Thailand, Denmark, and the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
93
1
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 34 publications
7
93
1
10
Order By: Relevance
“…The fact that Salmonella serotypes in animals were similar to those in humans (35)(36)(37) indicates the role of contaminated foods in the spread of Salmonella to humans. Interestingly, S. Schwarzengrund, which has been reported to be an internationally spread strain (38), was found in this study. A high percentage of E. coli contamination was also observed.…”
Section: Discussionsupporting
confidence: 44%
“…The fact that Salmonella serotypes in animals were similar to those in humans (35)(36)(37) indicates the role of contaminated foods in the spread of Salmonella to humans. Interestingly, S. Schwarzengrund, which has been reported to be an internationally spread strain (38), was found in this study. A high percentage of E. coli contamination was also observed.…”
Section: Discussionsupporting
confidence: 44%
“…High prevalence of nontyphoidal Salmonellae has also been reported from other parts of the world [22][23][24], indicating that infections with non-typhoidal Salmonellae are a global problem. Infections due to multidrug resistant S. enterica serotype Typhi have also been regarded as major problems in several parts of the world [25].…”
Section: Discussionmentioning
confidence: 81%
“…Such resistance is the cause of therapeutic failure against the pathogen, and increase infection severity and recovery time (Angkititrakul et al 2005). Aarestrup et al (2007) reported 89 % of Salmonella isolates from chicken meat in Thailand, were found resistance to nalidixic acid. The S. enterica isolate in the current study also showed resistance against nalidixic acid.…”
Section: Discussionmentioning
confidence: 99%